Liposome-integrated seawater reverse osmosis membrane prepared via facile spray-assisted interfacial polymerization - Lai, Gwo Sung (2022)
In this work, we demonstrated the effectiveness of using spray-assisted interfacial polymerization (IP) technique in fabricating liposome-integrated thin film nanocomposite (TFN) membranes for seawater reverse osmosis (SWRO). The liposome loading within the selective polyamide (PA) layer of the TFN membrane can be precisely controlled by manipulating spraying conditions to eliminate the wastage of precious additives compared to the conventional blending method. Spraying the liposomes after applying the aqueous phase of M-phenylenediamine (MPD) could prevent the loss and disruption of liposome distribution over the substrate layer. Upon incorporating 4 mg/m2 of liposomes, the best-performing S4-a membrane is able to achieve 27% higher water permeability than the liposome-free membrane, demonstrating a permeability of 3.24 L/m2·h·bar along with 99.3% NaCl rejection for seawater desalination. Characterization showed that dynamic liposomes had affected the IP process by creating a larger miscible reaction zone for IP, which led to the formation of a rougher PA surface with more nanovoids in the ultra-thin selective layer, thus, contributing to higher effective surface area and less hydraulic resistance for improving water permeability. An additional PVA layer was coated atop the liposome-integrated membrane to effectively improve the membrane stability and fouling resistance, leading to a comparable level of salt rejection with the state-of-the-art commercial membranes in treating real seawater, while water permeability was enhanced by 26–185%. This work presents a readily scalable spray-assisted IP technique to fabricate liposome-integrated SWRO membrane for seawater desalination.